Numerical study of Cs2TiX6 (X = Br−, I−, F− and Cl−) based perovskite solar cell using SCAPS-1D device simulation. (December 2019) - Chakraborty, Kunal; Choudhury, Mahua Gupta; Paul, Samrat
Graphical abstract: Highlights: Optimization performance parameters of CuSCN/Cs2 TiX6 /CdS/Si solar cell structure for Absorbing layer thickness, Device working temperature, Quantum efficiency and Series resistance are studied through SCAPS-1D simulator. Abstract: The present work represents the study of numerical simulation of Cesium Titanium (IV) Halide thin film based lead-free Perovskite Solar Cells (PSCs) using Solar Cell Capacitance Simulator (SCAPS). For this study, an alternative inorganic material cell architecture CuSCN/Cs2 TiX6 /CdS/Si has been proposed, where X is halide like Br, I, F and Cl. The effects of variation in absorbing layer thickness and device working temperature on the solar cell performance were simulated through SCAPS simulator. This simple cell architecture has helped us to study and optimize the device parameters. The 1D optimization for the proposed lead-free Perovskite based solar cell resulted in optimized active layers thickness, device temperature and quantum efficiency for Cs2 TiBr6, Cs2 TiI6, Cs2 TiF6 and Cs2 TiCl6 active materials. The study resulted in optimized thickness of 1.0 µm, 1.5 µm, 1.5 µm and 1.5 µm for Cs2 TiBr6, Cs2 TiI6, Cs2 TiF6 and Cs2 TiCl6 active materials, respectively. The optimized device temperature was found to be at 80 °C for Cs2 TiBr6, 60 °C for Cs2 TiI6, 75 °C for Cs2 TiF6 and 75 °C for Cs2 TiCl6 .